Overweight and Obesity: its Impact on Foot Type, Flexibility, Foot Strength, Plantar Pressure and Stability in Children from 5 to 10 Years of Age: Descriptive Observational Study. - Molina-García, Cristina; Jiménez-García, José Daniel; Velázquez-Díaz, Daniel; Ramos Petersen, Laura; López-del-Amo-Lorente, Andrés; Martínez-Sebastián, Carlos; Álvarez-Salvago, Francisco (MDPI, 2023)
Background: Overweight (OW) and childhood obesity (OB) may cause foot problems and affect one’s ability to perform physical activities. The study aimed to analyze the differences in descriptive characteristics, foot type, laxity, foot strength, and baropodometric variables by body mass status and age groups in children and, secondly, to analyze the associations of the BMI with different physical variables by age groups in children. Methods: A descriptive observational study involving 196 children aged 5–10 years was conducted. The variables used were: type of foot, flexibility, foot strength and baropodometric analysis of plantar pressures, and stability by pressure platform. Results: Most of the foot strength variables showed significant differences between the normal weight (NW), OW and OB groups in children aged between 5 and 8. The OW and OB groups showed the highest level of foot strength. In addition, the linear regression analyses showed, in children aged 5 to 8 years, a positive association between BMI and foot strength (the higher the BMI, the greater the strength) and negative association between BMI and stability (lower BMI, greater instability). Conclusions: Children from 5 to 8 years of age with OW and OB show greater levels of foot strength, and OW and OB children from 7 to 8 years are more stable in terms of static stabilometrics. Furthermore, between 5 and 8 years, having OW and OB implies having more strength and static stability.
Keywords: Obesidad en niños; Podología pediátrica; Pediatric obesity; Children; Plantar pressure; Static stability